Heat integration of methanol steam reformer with a high-temperature polymeric electrolyte membrane fuel cell. (1st February 2017) - Ribeirinha, P.; Alves, I.; Vázquez, F. Vidal; Schuller, G.; Boaventura, M.; Mendes, A.
Abstract: A fuel cell is an exothermic device that wastes ca. 50% of the input chemical energy while methanol steam-reforming (MSR) reaction is endothermic. The integration of a low temperature methanol steam-reforming cell (MSR-C) with a high temperature polymer electrolyte membrane fuel cell (HT-PEMFC) in a combined stack arrangement allows the thermal integration of both reactors. A novel bipolar plate of poly(p-phenylene sulfide) (PPS) featuring the fuel cell flow field in one side and the reformer flow field in the other was designed, built and assessed. For the first time are reported high current densities (>0.5 A cm −2 ) with the integrated system running at 453 K. The system was also ran for more than 100 h at 453 K, at 0.3 A cm −2, with a methanol conversion of >90%. It was observed some degradation of the membrane electrode assembly (MEA) due to the continuous presence of methanol in the reformate stream. Electrochemical impedance spectroscopy (EIS) analyses revealed an overall increase of the resistances. The self-thermal sustainability of the combined device was only reached for >0.75 A cm −2 due to the poor thermal insulation of the combined reactor. Highlights: A novel bipolar plate made of PPS for integrating MSR-C/HT-PEMFC was designed. High performances were achieved with the integrated MSR-C/HT-PEMFC at 453 K. The thermal integration can improve the energy efficiency.